2013
DOI: 10.2989/1814232x.2013.829788
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rights-based management of small pelagic fish within an ecosystems approach to fisheries in South Africa

Abstract: Hara, M. (2013). Efficacy of rights-based management of small pelagic fish within an ecosystems approach to fisheries in South Africa. Abstract South Africa's small pelagics fishery is moving towards a management strategy using an ecosystem approach to fisheries (EAF), with rights-based management (RBM) as the key rights allocation system. While EAF strives to balance between, among others, ecological and social-economic objectives, RBM is driving the sector towards economic efficiency. Within EAF itself, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Discarding is mainly policy or market driven. Policy measures such as legal landings sizes or catch quota may forbid selling small fish (Harley et al 2000;Rochet and Trenkel 2005;Depestele et al 2011;Feekings et al 2012) or over-quota catches (Copes 1986;Branch 2009;Poos et al 2010), while market incentives prevent the sale of certain (by-catch) species or size classes (Gray and Kennelly 2003;Hara 2013;Eliasen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Discarding is mainly policy or market driven. Policy measures such as legal landings sizes or catch quota may forbid selling small fish (Harley et al 2000;Rochet and Trenkel 2005;Depestele et al 2011;Feekings et al 2012) or over-quota catches (Copes 1986;Branch 2009;Poos et al 2010), while market incentives prevent the sale of certain (by-catch) species or size classes (Gray and Kennelly 2003;Hara 2013;Eliasen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In most countries where ITQs have been implemented, it has been demonstrated that this approach can increase economic efficiency (Grafton, 1996;Dewees, 1998;World Bank, 2009;Sumaila, 2010). At the same time one of the negative consequences of ITQs is that they can result in negative social costs especially on coastal communities that might be solely dependent on the fishing industry (McCay, 1998;Hara, 2013). For example, in Iceland, small fishing communities lost a large relative share of the quota resulting in increased financial problems and unemployment (Arnason, 2005).…”
Section: Rights Based Managementmentioning
confidence: 99%
“…The requirement for active and meaningful stakeholder participation in management is part of one of EAF's three top objectives -'Ability to achieve ' (FAO 2003;Petersen et al 2010). This was supposed to be enhanced through implementation of long-term rights (Hara 2013).…”
Section: The Small-pelagics Fishing Sectormentioning
confidence: 99%